Atmospheric Corrosion Inhibition of Steel Using Tea Leaf Extract in the Coastal Environment of Air Tawar, Padang - Niko Kurniawan; Sabrizal Saputra; Dinalia Dinalia; Yerimadesi Yerimadesi; sauli safitri (Jurnal Akademika Kimia, 2025)
This study evaluates the effectiveness of tea leaf extract as a corrosion inhibitor for steel under real coastal atmospheric exposure. The novelty of this work lies in its direct assessment of a plant-derived inhibitor in an open-air marine environment, a setting that has not been adequately addressed in previous studies, which have largely focused on controlled aqueous systems. In addition, this study employs mature tea leaves, an abundant agricultural byproduct with naturally high tannin content, processed through a simple, solvent-free extraction method, thereby offering a sustainable route for green inhibitor development. The extract was obtained from mature tea leaves through aqueous boiling, and its tannin content was quantified using UV–Vis spectrophotometry. ASSAB 760 steel specimens were coated by immersion in tea extract at varying concentrations and soaking durations, followed by natural exposure in a coastal environment for 1 to 30 days. Corrosion behavior was evaluated using the weight loss method. The results showed that mature tea leaves contained the highest tannin concentration (29530.95 ppm), supporting their selection for inhibitor application. The optimum extract concentration was identified as 11000 ppm with a 5-hour immersion time. Under these conditions, treated steel exhibited a substantially lower corrosion rate (7.78 × 10⁻⁵ g/cm²/day) compared to untreated steel (1.66 × 10⁻⁴ g/cm²/day), corresponding to a maximum inhibition efficiency of 84.71%. The inhibition mechanism is attributed to the formation of a stable Fe³⁺–tannin chelate complex that adsorbs onto the steel surface, forming a protective film that restricts the ingress of aggressive chloride-rich moisture in the coastal atmosphere. Overall, the findings demonstrate the practical viability of mature tea leaf extract as an effective and environmentally benign atmospheric corrosion inhibitor, providing field-relevant insight into sustainable protection strategies for marine-exposed steel infrastructure.